2023
DOI: 10.1002/nop2.1589
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the current status of community nurses' spiritual care competencies and the factors: A descriptive cross‐sectional analysis

Abstract: Aim To examine and analyze the level of spiritual care competency among community nurses. Design The study employed a cross‐sectional design. Methods From May to July 2022, 442 nurses from community health clinics were chosen as survey respondents using the convenience sample method. The General Information Questionnaire, the version in Chinese of the Nurses' Spiritual Caregiving Awareness Scale and the Chinese version of the Spiritual Caregiving Competence Scale were used in the survey. There were 442 questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Additionally, this result was consistent with a study on the "Effect of educational program regarding therapeutic exercises for women undergoing mastectomy," (22) which noted that the majority of the analyzed samples were women between the ages of 40 and 55. Concerning marital status, the present study revealed that the majority of the studied group was married; this result is in line with Zhang X. et al (2023) (23) , who reported that most breast cancer women were married. Concerning the educational level, the findings of the present study revealed that 44% of the VR group and half of the booklet group had basic education.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, this result was consistent with a study on the "Effect of educational program regarding therapeutic exercises for women undergoing mastectomy," (22) which noted that the majority of the analyzed samples were women between the ages of 40 and 55. Concerning marital status, the present study revealed that the majority of the studied group was married; this result is in line with Zhang X. et al (2023) (23) , who reported that most breast cancer women were married. Concerning the educational level, the findings of the present study revealed that 44% of the VR group and half of the booklet group had basic education.…”
Section: Discussionsupporting
confidence: 92%
“…Past literature [49] used a censored version of the Chinese version of the scale, and diferent authors have diferent interpretations and expressions of the Chinese version of the SCC scale. (2) Education and religion have been found to be infuencing factors of SCC [52]. Participants in the prior study [51] had undergraduate (bachelor's) degrees, and religious beliefs in Iranian society were fruitful in developing students' spiritual care skills [51].…”
Section: Discussionmentioning
confidence: 99%